2013
DOI: 10.1590/s0080-62342013000100008
|View full text |Cite
|
Sign up to set email alerts
|

Pacientes em uso de quimioterápicos: depressão e adesão ao tratamento

Abstract: This analy cal, cross-sec onal study applied a quan ta ve approach to verify the presence of depression and the adherence to a chemotherapy treatment in pa ents with cancer at the central chemotherapy pharmacy of a university hospital. The sample consisted of 102 pa ents, and data were collected from October 2010 to May 2011. A structured interview was used to obtain sociodemographic, clinical and therapeu c data; the Morisky Test and Beck Depression Inventory were also applied. The results revealed that 10.8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
28

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 15 publications
0
11
0
28
Order By: Relevance
“…As relações estabelecidas através dos diálogos individuais entre os adoecidos, e entre eles e os participantes do grupo de extensão, foram perceptíveis na articulação da dinâmica do grupo, pois pessoas que não eram tão participativas, depois de algumas reuniões se sentiam confiantes em compartilhar suas experiências e enriqueciam nosso debate com seus relatos (8) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…As relações estabelecidas através dos diálogos individuais entre os adoecidos, e entre eles e os participantes do grupo de extensão, foram perceptíveis na articulação da dinâmica do grupo, pois pessoas que não eram tão participativas, depois de algumas reuniões se sentiam confiantes em compartilhar suas experiências e enriqueciam nosso debate com seus relatos (8) .…”
Section: Discussionunclassified
“…Quanto ao ato de ouvir, como descrevem alguns pesquisadores e como podemos evidenciar em nossa vivência, percebemos que o paciente com câncer tende a não falar sobre os seus medos e o cuidador a não questioná-lo, não associando os distúrbios do sono, a falta de apetite, queda de cabelo, perda da energia, fadiga, dor, como fatores que interferem no autocuidado, acarretando um déficit de adesão ao tratamento e agravando dessa forma o prognóstico da doença (8) .…”
Section: Discussionunclassified
“…In a study of 44 patients with stage IV colorectal cancer receiving chemotherapy, manifestations of toxicity, such as fatigue and insomnia, were identified. [8] Another study conducted in 102 cancer patients identified moderate and severe depression in 10.8% and 1.9%, respectively, due to the use of antineoplastic therapies [9] and therefore, founded non-adherence to treatment in 48% of patients. [9] An observational study of 100 patients with advanced colorectal cancer treated with palliative chemotherapy identified symptoms of fatigue, pain, dyspnea, and appetite loss.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Another study conducted in 102 cancer patients identified moderate and severe depression in 10.8% and 1.9%, respectively, due to the use of antineoplastic therapies [9] and therefore, founded non-adherence to treatment in 48% of patients. [9] An observational study of 100 patients with advanced colorectal cancer treated with palliative chemotherapy identified symptoms of fatigue, pain, dyspnea, and appetite loss. In addition, the quality of life was deteriorated across time, thus it was found large differences between patients with and without a treatment response for pain (19.0 vs. 37.2 points) and appetite loss (17.4 vs. 32.7 points).…”
Section: Introductionmentioning
confidence: 99%
“…As alterações do pensamento e do comportamento inerentes aos sintomas depressivos podem influenciar tanto somaticamente, agravando os sintomas físicos do câncer de mama quanto psicologicamente o que gera prejuízo funcional, menor adesão terapêutica, piora da qualidade de vida, pior prognóstico e consequentemente elevam as taxas de morbidade e mortalidade (SOUZA, 2013).…”
Section: Introductionunclassified